Toxicity of Biologically Active Peptides and Future Safety Aspects: An Update - Khan, Fazlullah; Niaz, Kamal; Abdollahi, Mohammad (Current Drug Discovery Technologies, 2018)
Introduction: Peptides are fragments of proteins with significant biological activities. These peptides are encoded in the protein sequence. Initially, such peptides are inactive in their parental form, unless proteolytic enzymes are released. These peptides exhibit various functions and play a therapeutic role in the body. Objective: Besides the therapeutic and physiological activities of peptides, the main purpose of this study was to highlight the safety aspects of peptides. Method: We performed an organized toxicity and search of available literature using PubMed, Google Scholar, Medline, EMBASE, Reaxys and Scopus databases. All the relevant citations including research and review articles about the toxicity of biologically active peptides were evaluated and gathered in this study. Result: Biological peptides are widely used in the daily routine ranging from food production to the cosmetics industry and also they have a beneficial role in the treatment and prevention of different diseases. These peptides are manufactured by both chemical and biotechnological techniques, which show negligible toxicity, however, some naturally occurring peptides and enzymes may induce high toxicity. Depending upon the demand and expected use in the food or pharmaceutical industry, we need different approaches to acertain the safety of these peptides preferentially through in silico methods. Conclusion: Intestinal wall disruption, erythrocytes and lymphocytes toxicity, free radical production, enzymopathic and immunopathic tissue damage and cytotoxicity due to the consumption of peptides are the main problems in the biological system that lead to various complicated disorders. Therefore, before considering biologically active peptides for food production and for therapeutic purpose, it is first necessary to evaluate the immunogenicity and toxicities of peptides.
Keywords: computational biology